ปัจจัยที่ส่งผลต่อการมีส่วนร่วมในการเรียนวิชาชีพหลักสูตรระยะสั้นของนักศึกษาผู้ใหญ่ศูนย์การศึกษานอกโรงเรียน กรุงเทพมหานคร - ณัฏฐลักษณ์ ศรีมีชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this thesis were (1) to study the level of adult learners’ participation in vocational short courses in non-formal education centers in Bangkok metropolis, (2) to study factors affecting adult learners participation in vocational short courses in non-formal education centers in Bangkok metropolis, (3) to identify predictor variables of participating in vocational short courses. The samples were 246 adult learners of vocational short courses in non-formal education centers, Bangkok metropolis. Questionairs were used as research instrument. The percentage, mean, standard deviation and multiple regression analysis were used for data analysis. The findings revealed that : 1. The levels of adult learners participation were at the moderate level ([Mean] = 2.95 ) in vocational short courses in the survey of problems, the planning, the implementation, and the evaluation. 2. Factors affecting adult learners participation in vocational short courses at .01 level of significant were two variables : institutional environment and areas of vocational short courses. Factor affecting adult learners participation in vocational short courses at .05 level of significant was only one variable which was the level of education. 3. Two selected variables could predict adult learners participation in vocational short courses at 19.40 percents by the stepwise method which were institutional environment and areas of vocational short courses.